Covid-19, ; Covid-19, unequal economic recovery and maritime food trade - Maximilian Heigermoser; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2021)
2020 Covid-19 . , , - , . 2020 , . , , , 11 . , . 2020 (). . , , . . , , - , , . – – The Covid-19 pandemic poses unprecedented challenges to the global economy. While aggregated agricultural trade patterns remained largely unaffected by the pandemic, the World Bank still expects global poverty to rise for the first time in more than twenty years. Since late 2020, several developments have the potential to further jeopardize global food security. Precisely, sea freight rates for bulk carriers, which are primarily used in international agricultural trade, have surged to an eleven-year high. However, despite the significant role that transportation costs play in international food trade, current research tends to overlook the impact they have on trade flows and food price formation. Further, the Food Price Index provided by the Food and Agriculture Organization of the United Nations (FAO) has increased for eleven straight months, reaching a seven-year high. These developments constitute increased risk to food security, particularly in poorer regions. Only strengthened international cooperation and unrestricted trade can safeguard global food security in the coming phase of globally uneven economic recovery. Calls for domestic self-sufficiency, proposals to transition to an over-bureaucratized, command-and-control EU-food system, as well as tightening economic sanctions and countersanctions between leading economic powers endanger food security, especially in import-dependent regions.
urn:nbn:de:gbv:3:2-137539
Keywords: 330